(untitled) (Orfeu, 2021)
This article aims to discuss the training of teachers from experiences developed through supervised internship in music during the period of emergency remote teaching. The theoretical framework was constituted from the following themes: digital technologies and social media, collaborative learning and training for music teaching. The methodology used was action research. The undergraduates were encouraged to develop an internship proposal that culminated in the collaborative production and application of a virtual musical-pedagogical material in at school. Reflections were established on the role of the supervised internship in new contexts and scenarios from the realization and implementation of this material, as well discuss the implications for the professionalization of these undergraduates. The impressions revealed score positively for the collaborative construction of educational proposals based on the identification, elaboration, realization, performance and reflection, being an essential part for the understanding of the formation of music teaching in contemporaneity.